EFEKTIVITAS PEMBELAJARAN MODEL PROBLEM BASED LEARNING (PBL) DALAM MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA - meidha zulva fadhila (Civic Edu : Jurnal Pendidikan Kewarganegaraan, 2025)
In the learning process in the classroom is expected to be student-centered, which requires the right learning model for optimal learning outcomes, the right learning model is a student-centered learning model, this study applies the Problem Based Learning (PBL) learning model in the learning process in class XIII SMP Negeri 2 Pagelaran, this study aims to determine the effect of the Problem Based Learning (PBL) learning model on student learning outcomes in learning Pancasila Education class XIII SMP Negeri 2 Pagelaran. The research method used is quasi experiment with pre-experimental design method design type one group pretest-posttest, the instrument in this study is a multiple choice test question containing 30 questions, The data were analyzed using the Mann-Whitney test through SPSS 26. The results of the analysis showed that the value of Asymp. Sig. (2-tailed) value of 0.001 <0.05, which means There is a significant difference between the experimental group using the PBL learning model and the control group using conventional methods. Thus, it can be concluded that the PBL learning model has a significant effect on improving student learning outcomes. This finding indicates that choosing the right learning model, such as PBL, plays a significant role in improving student learning outcomes. Therefore, teachers need to consider each learning model with the material and student characteristics to achieve optimal learning outcomes.